Surface Modification of Sulfur Cathodes with PEDOT:PSS Conducting Polymer in Lithium-Sulfur Batteries - Lee, Jeongyeon; Choi, Wonchang (ELECTROCHEMICAL SOC INC, 2015)
Sulfur powder was coated with poly(3,4-ethylenedioxythiophene)-polystyrenesulfonie acid (PEDOT:PSS) using a wet mixing process in water. The modified sulfur material was investigated for use as a cathode in lithium-sulfur (Li-S) batteries. The surface modification with the conducting polymer was identified with Fourier transform infrared (FTIR) spectra, scanning electron microscopy (SEM), and high-resolution transmission electron microscopy (HR-TEM) analyses. Electrochemical evaluation revealed that surface modification with PEDOT:PSS leads to increases in initial capacity and improvements in the rate capability and cyclability of sulfur electrodes. Electrochemical impedance spectroscopy (EIS) measurements certified a decreased resistance of the PEDOT:PSS-coated sulfur electrode compared to a pure sulfur electrode, indicating that surface modification with a conducting polymer effectively enhanced the electrochemical performance of sulfur electrodes in Li-S batteries. (C) The Author(s) 2015. Published by ECS. All rights reserved.
Keywords: LI-S BATTERIES; PERFORMANCE; COMPOSITE; GRAPHENE